2020
DOI: 10.3390/nu12030650
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Choice and Health-Related Claims

Abstract: Scientific evidence shows that food consumption is one of the main causes that increases the risk of developing a non-communicable disease (NCD) [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…By the same token, the chemical composition of bottled and filtered water varies widely, and the adequate evaluation of the impact of any given water composition on human health is difficult. Thus, whereas a large number of studies have evaluated how different nutrients or nutritional regimes impact our health [13], studies on water are comparatively few and generally very limited in scope.…”
Section: Introductionmentioning
confidence: 99%
“…By the same token, the chemical composition of bottled and filtered water varies widely, and the adequate evaluation of the impact of any given water composition on human health is difficult. Thus, whereas a large number of studies have evaluated how different nutrients or nutritional regimes impact our health [13], studies on water are comparatively few and generally very limited in scope.…”
Section: Introductionmentioning
confidence: 99%
“…As for income, a positive interaction was found between higher income and functional food purchasing habits [60]. Finally, most of the literature has shown that women are the most interested and willing to pay more for functional foods and yoghurt [61,62].…”
Section: Functional Foods and Functional Yoghurtmentioning
confidence: 83%
“…These results are substantiated by Wardy et al (2018) [25], who showed that HBI increased the purchase intent with HBI. Petrun et al (2015) [26] and De Magistris (2020) [27] concluded that customers are willing to pay for health claims rather than nutrition claims. The effect of bread with fiber and HBI on panelist emotional terms is illustrated in Table 5.…”
Section: Sensory Properties and Emotions Of Optimized Gluten-free Bre...mentioning
confidence: 99%